Predicting Electron Population Characteristics in 2‐D Using Multispectral Ground‐Based Imaging. Issue 1 (4th January 2018) - Grubbs, Guy; Michell, Robert; Samara, Marilia; Hampton, Donald; Jahn, Jorg‐Micha
Abstract: Ground‐based imaging and in situ sounding rocket data are compared to electron transport modeling for an active inverted‐V type auroral event. The Ground‐to‐Rocket Electrodynamics‐Electrons Correlative Experiment (GREECE) mission successfully launched from Poker Flat, Alaska, on 3 March 2014 at 11:09:50 UT and reached an apogee of approximately 335 km over the aurora. Multiple ground‐based electron‐multiplying charge‐coupled device (EMCCD) imagers were positioned at Venetie, Alaska, and aimed toward magnetic zenith. The imagers observed the intensity of different auroral emission lines (427.8, 557.7, and 844.6 nm) at the magnetic foot point of the rocket payload. Emission line intensity data are correlated with electron characteristics measured by the GREECE onboard electron spectrometer. A modified version of the GLobal airglOW (GLOW) model is used to estimate precipitating electron characteristics based on optical emissions. GLOW predicted the electron population characteristics with 20% error given the observed spectral intensities within 10° of magnetic zenith. Predictions are within 30% of the actual values within 20° of magnetic zenith for inverted‐V‐type aurora. Therefore, it is argued that this technique can be used, at least in certain types of aurora, such as the inverted‐V type presented here, to derive 2‐D maps of electron characteristics. These can then be used to further derive 2‐D maps of ionospheric parameters as a function of time, based solely on multispectral optical imaging data. Key Points: Modified GLOW electron transport code produces electron characteristics within 20% of in situ measurements 10° from magnetic zenith The inferred electron characteristics are within 30% of measurements within 20° of magnetic zenith for inverted‐V‐type aurora Optical observations can be used to produce 2‐D maps of electron energy and flux and height‐integrated Hall and Pedersen conductivities